Post-fire soil erosion dynamics: effect of ash cover and slope factors - Edivaldo Lopes Thomaz; Paulo Angelo Fachin; Yasmmin Tadeu Costa; Valdemir Antoneli; Paulo Pereira (Discover Soil)
Abstract Purpose This study examined the hydrological and erosive responses of tropical soils in a slash-and-burn agricultural system, focusing on the effects of ash cover and slope. To isolate the influence of ash, it was retained on some plots and removed from others. The objectives were to: (1) assess whether ash cover affects runoff and soil erosion, (2) analyze the role of slope gradients (6° and 11°) on these processes, and (3) evaluate the effectiveness of erosion plots to monitor the effect of post-fire ash on erosion processes in the field. Materials and methods Field measurements over eight months (i.e., bean crop season) were conducted on twelve 1 m2 erosion microplots (0.5 m wide × 2 m long) under natural rainfall conditions. Results No significant differences were observed in soil loss or runoff between the treatments. The ash-covered and ash-removed plots were compared. Soil loss ranged from 110 to 1279 g m−2, with plots on a 6° slope losing 463 g m−2 on average and those on an 11° slope losing 258 g m−2. The runoff ranged from 14 to 107 L m−2, with an average of 40 L m−2. Approximately 40% of the ash was removed from the plots after three rain events, thereby limiting its protective effect. Conclusions These findings suggest that ash cover and slope do not significantly influence soil erosion or runoff in the study context. Although the study is limited by plot scale and short-term monitoring, it provides valuable insights into ash-soil interactions and highlights the need for further research on long-term impacts and variable fire severities.